Adapting Medication for Type 2 Diabetes to a Low Carbohydrate Diet - Cucuzzella, Mark; Riley, Karen; Isaacs, Diana (Frontiers in Nutrition, 2021)
Healthcare professionals need to be competent to safely adapt diabetes medications when patients with Type 2 Diabetes (T2D) alter their diet. Safe prescribing is supported through an understanding of the clinical evidence, basic science, and pharmacology of medications. This review article supports clinicians in the practical application of this knowledge to achieve safe practice. Traditional medical training and clinical practice for chronic disease has revolved around the teaching of intensifying therapy and evidence based prescribing, a crucial skill when chronic disease progresses. We are now witnessing remission of Type 2 Diabetes through low carbohydrate diets (LCD). We must apply the same effort and thought to de-prescribing as the underlying metabolic condition improves. There is minimal guidance in the literature on de-prescribing. The American Diabetes Association in their Standards of Medical Care in Diabetes—2021 acknowledges LCD as a viable option in the management of T2D. Thus, the goal of our paper is to help close the gap between the clinical evidence, basic science, and pharmacology of T2D medications to the practical application and teamwork needed to facilitate safe medication reduction when applied to a LCD. The LCD is an increasingly popular and effective option for managing T2D and can lead to an improvement in the condition, reduced medication burden, and contribute to significant weight loss. Safe initiation of a LCD in patients on medications requires significant monitoring and medication adjustments to decrease and eliminate the risk of hypoglycemia and hypotension. The health care team including clinicians in primary care, nursing, pharmacy and nutrition need to be competent in adjusting diabetes and antihypertensive medications to achieve safe and effective care. The most immediate and important adjustments are to insulin, sulfonylureas, SGLT2 inhibitors, blood pressure medications and diuretics. Interdisciplinary care teams can individualize therapy while following the guidance above, which includes monitoring glucose and blood pressure closely, decreasing medications that can cause hypoglycemia and hypotension, evaluating glucose and blood pressure data regularly, and open access communication with the team. Article is an international consensus document on de-prescribing that was put together by a multidisciplinary team of clinicians.